FENOMENA MANAJEMEN PERUBAHAN PENDIDIKAN ISLAM TRANSFORMATIF - M. Zen Ma'arif; Binti Maunah; Asrop Safi’i (As-Sulthan Journal of Education, 2026)
This study examines the phenomenon of change management in transformative Islamic education as a response to global disruption, the Industrial Revolution 4.0, and Society 5.0. The purpose of the study is to analyze how the principles of change management can be integrated with Islamic spiritual values to build educational institutions that are adaptive while remaining grounded in tawhid. The research employs a descriptive qualitative approach based on a literature review, utilizing content analysis and conceptual synthesis of various scholarly sources, including books and recent academic journals. The findings indicate that the success of change management in Islamic educational institutions depends on three main aspects: transformational leadership, managerial competence, and effective instructional supervision. The integration of modern change theories—such as the models proposed by Kurt Lewin and Kotter—with Islamic values such as tazkiyah, islah, and tajdid gives rise to a management system that is not only efficient but also spiritual and oriented toward the common good (maslahah). Other supporting factors include the use of educational technology, adaptive organizational restructuring, and a collaborative work culture. This study contributes to the field of Islamic educational management by offering a new theoretical framework that emphasizes that genuine educational transformation can only be realized through the synergy between modern managerial systems and prophetic Islamic ethics.